HUBUNGAN SELF EFFICACY DENGAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VIID MTSN 13 PESISIR SELATAN - ridha ulfahmi yessa; rahmi rahmi; hafizah delyana (Department of Mathematics Education, Universitas Kuningan, 2022)
Mathematical communication is a high level skill that students have acquired. Students' self efficacy is required to boost their learning confidence. The goal of this study was to see if there was a link between self efficacy and mathematical communication skills in Pesisir Selatan’s class VII D MTsN 13. This type of research is quantitative which is classified as correlational. The subjects of this study were 26 students were selected purposive sampling. A self efficacy test and a mathematical communication test were utilized to collect data in this study. This study’s data analysis method includes a simple linear regression test, a correlation test, and a hypothesis test utilizing the t test. Based the analysis it’s indicating that the linear relationship between X and Y is weak, and the analysis concluded that there is a weak but not significant relationship between self efficacy students’ mathematical communication skills in class VII D MTsN 13 Pesisir Selatan. After being traced through interviews, it was found that students were weak in understanding concepts, this was indicated by some students still confused with the use the right concepts in solving the problem given.